The accuracy of German citizens’ confidence in their climate change knowledge - Fischer, Helen; Amelung, Dorothee; Said, Nadia (Nature climate change, 2019)
Whether citizens are able to reject false information about climate change may depend on their confidence in their existing knowledge. This study shows that German citizens are less confident in their climate change knowledge than they should be based on their actual knowledge.